A cDNA cloning vector that permits expression of cDNA inserts in mammalian cells. - Okayama, H (1983)
This paper describes a plasmid vector for cloning cDNAs in Escherichia coli; the same vector also promotes expression of the cDNA segment in mammalian cells. Simian virus 40 (SV40)-derived DNA segments are arrayed in the pcD vector to permit transcription, splicing, and polyadenylation of the cloned cDNA segment. A DNA fragment containing both the SV40 early region promoter and two introns normally used to splice the virus 16S and 19S late mRNAs is placed upstream of the cDNA cloning site to ensure transcription and splicing of the cDNA transcripts. An SV40 late region polyadenylation sequence occurs downstream of the cDNA cloning site, so that the cDNA transcript acquires a polyadenylated 3' end. By using pcD-alpha-globin cDNA as a model, we confirmed that the alpha-globin transcript produced in transfected cells is initiated correctly, spliced at either of the two introns, and polyadenylated either at the site coded in the cDNA segment or at the distal SV40 polyadenylation signal. A cDNA clone library constructed with mRNA from SV40-transformed human fibroblasts and this vector (about 1.4 X 10(6) clones) yielded full-length cDNA clones that express hypoxanthine-guanine phosphoribosyltransferase (Jolly et al., Proc. Natl. Acad. Sci. U.S.A., in press).